2003
DOI: 10.1079/bjn2003990
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of preschool Senegalese children: long-term effects of early severe malnutrition

Abstract: The prevalence of malnutrition remains high in many developing countries. However, data relating to the long-term effects of severe malnutrition, specifically, serum levels of biochemical indicators of nutritional status, are still scarce in the literature. Hence the present study aimed to investigate the nutritional, biological and growth status of Senegalese preschool children previously hospitalised for severe malnutrition. The study involved twenty-four 7-year-old children who had suffered from marasmus 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
2
20
0
1
Order By: Relevance
“…In our experiments, although no difference was found either in the mean number of macrophages harvested from the peritoneal cavity or in the differential counts of peripheral blood leukocytes between NPD and LPD animals, the early undernutrition produced an alteration in red blood cells that was not completely restored even after a normal protein diet was supplied. Our findings are in agreement with those reported by Idohou-Dossou et al (34) who observed a decrease in hematological parameters of Senegalese preschoolers who had suffered from marasmus after birth. Impairment of bone marrow cell proliferation in animals and humans undernourished in pregnancy or after birth is well documented in the literature but there are few studies exploring the long-term effects.…”
Section: Discussionsupporting
confidence: 94%
“…In our experiments, although no difference was found either in the mean number of macrophages harvested from the peritoneal cavity or in the differential counts of peripheral blood leukocytes between NPD and LPD animals, the early undernutrition produced an alteration in red blood cells that was not completely restored even after a normal protein diet was supplied. Our findings are in agreement with those reported by Idohou-Dossou et al (34) who observed a decrease in hematological parameters of Senegalese preschoolers who had suffered from marasmus after birth. Impairment of bone marrow cell proliferation in animals and humans undernourished in pregnancy or after birth is well documented in the literature but there are few studies exploring the long-term effects.…”
Section: Discussionsupporting
confidence: 94%
“…These observations suggest that blood containing malaria parasites and reduced IGF1 levels may be more infective to mosquitoes than blood containing parasites with IGF1 levels in a range consistent with less severe infection. Given that low levels of IGF1 have also been linked with severe malnutrition (Idohou-Dossou et al, 2003;Stephenson et al, 2000;Gomes et al, 2007), our work suggests that poor nutritional status may compound the effects of IGF1 on malaria transmission, such that efforts to improve nutrition may have an added epidemiological benefit of maintaining higher IGF1 levels that reduce parasite transmission to the mosquito host.…”
Section: Discussionmentioning
confidence: 95%
“…Protein energy malnutrition (PEM) is a common condition in most developing countries especially in Africa including Nigeria (Nnakwe, 1995), Senegal (Idohou-Dossou et al, 2003) and in most of the war ravaged countries such as Somalia and Sudan in Africa and Thailand in Asia. It occurs as a result of lack of quality protein food, poverty, faulty weaning process, poor sanitary conditions and mal-*Corresponding author.…”
Section: Introductionmentioning
confidence: 99%